PEMBERIAN KOMBINASI BEBERAPA JENIS TANAMAN OBAT SEBAGAI UPAYA PENINGKATAN PRODUKTIVITAS AYAM PETELUR - Melkianus Luji Jadi; Cardial L. Penu; IGK Oka Wirawan (Partner, 2009)
Combination Gift Several Medicine Plants Kinds As Chicken Productivity Enhanced Efforts. A research to study layer productivity given traditional herbs with differences given frequency. Ras layer on after peak of production at 36-40weeks were used in this research. The research was arranged in a Completely Randomized Design with four treatments and five replications. The treatments were P0 = without traditional herbs as a control; P1 = one traditional herbs capsule everyday; P2 = one traditional herbs capsule every two days; and P3 = one traditional herbs  capsule  every four  days.  Data  were  analyzed  using  Proc.  ANOVA  (SAS institute, 2000) and further tested using Duncan’s Multiple Range Test (DMRT).Results  showed  that  the  treatments  affected  significantly  (P<0,01)  the  egg production and (P<0,05) the measurement of  eggs, but not significantly for egg weight. It is concluded that the traditional herbs will optimize the layer productionon after peak of production. Keywords: traditional herbs, egg production, egg weight, measurement of egg